2018
DOI: 10.1002/jbm4.10074
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐Asian Phase I Study of the Anti‐Fibroblast Growth Factor 23 Monoclonal Antibody, Burosumab: Safety and Pharmacodynamics in Adults With X‐linked Hypophosphatemia

Abstract: X‐linked hypophosphatemia (XLH) is a disease caused by abnormally elevated FGF23 levels, which cause persistent hypophosphatemia accompanied by subsequent reduction in bone mineralization that presents as rickets or osteomalacia. Burosumab is a fully human monoclonal antibody targeting FGF23 that is under development for the treatment of FGF23‐related hypophosphatemia including XLH. The safety, tolerability, and proof of concept of burosumab have been evaluated in patients with XLH in previous studies conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The study concluded that treatment with burosumab not only improved serum phosphorus levels but also positively impacted osteoarthritis indices and fracture healing when compared to placebo. Cheong et al reproduced similar results in a multicenter, sequential dose-escalation, open-label, single-dose study in Japanese and Korean adults with XLH [ 19 ].…”
Section: Discussionmentioning
confidence: 61%
“…The study concluded that treatment with burosumab not only improved serum phosphorus levels but also positively impacted osteoarthritis indices and fracture healing when compared to placebo. Cheong et al reproduced similar results in a multicenter, sequential dose-escalation, open-label, single-dose study in Japanese and Korean adults with XLH [ 19 ].…”
Section: Discussionmentioning
confidence: 61%
“…The WOMAC measures of physical functioning and stiffness were both found to be significantly improved by burosumab (14). A first-in-Asian trial showed similar biochemical responses with no signal for increased risk in a Japanese/Korean cohort (18).…”
Section: Adult Clinical Trials For Treating Xlh With Burosumabmentioning
confidence: 90%
“…Two phase 1 adult studies concluded that a single injection of burosumab is sufficient to significantly increase the tubular reabsorption rate of phosphate regardless of SC or IV administration. 13,14 There were no recorded increases of nephrocalcinosis, serum parathyroid hormone, or creatinine. Additionally, hypercalciuria, hypercalcemia, nor burosumab antibody formation occurred after the administration of a single dose.…”
Section: Pharmacodynamicsmentioning
confidence: 93%